The Role of Relationship Dynamics and Gender Inequalities As Barriers to HIV-Serostatus Disclosure: Qualitative Study among Women and Men Living with HIV in Durban, South Africa - Bhatia, Divya S.; Harrison, Abigail D.; Kubeka, Muriel; Milford, Cecilia; Kaida, Angela; Bajunirwe, Francis; Wilson, Ira B.; Psaros, Christina; Safren, Steven A.; Bangsberg, David R.; Smit, Jennifer A.; Matthews, Lynn T. (Frontiers in Public Health, 2017)
Background: This qualitative study investigated gender power inequalities as they contribute to relationship dynamics and HIV-serostatus disclosure among men and women living with HIV in Durban, South Africa. HIV-serodiscordance among men and women within stable partnerships contributes to high HIV incidence in southern Africa, yet disclosure rates remain low. Given the emphasis on prevention for HIV-serodiscordant couples, this research supports the urgent need to explore how best to support couples to recognize that they are part of this priority population and to access appropriate prevention and treatment. Methods: Thirty-five in-depth individual interviews were conducted with 15 HIV-positive men and 20 HIV-positive women (not couples) receiving care at public-sector clinics near Durban. A structured coding scheme was developed to investigate men’s and women’s attitudes toward HIV-serostatus disclosure and behaviors of sharing (or not sharing) HIV-serostatus with a partner. Narratives were analyzed for barriers and facilitators of disclosure through the lens of sociocultural gender inequality, focusing on reasons for non-disclosure. Results: Among 35 participants: median age was 33 (men) and 30 years (women); average years since HIV diagnosis was 1 (men) and 1.5 (women). Four themes related to gender inequality and HIV-serostatus disclosure emerged: (1) Men and women fear disclosing to partners due to concerns about stigma and relationship dissolution, (2) Suspicions and mistrust between partners underlies decisions for non-disclosure, (3) Unequal, gendered power in relationships causes differential likelihood and safety of disclosure among men and women, and (4) Incomplete or implicit disclosure are strategies to navigate disclosure challenges. Findings illustrate HIV-serostatus disclosure as a complex process evolving over time, rather than a one-time event. Conclusions: Partner communication about HIV-serostatus is infrequent and complicated, with gender inequalities contributing to fear, mistrust and partial or implicit disclosure. Relationship dynamics and gender roles shape the environment within which men and women can engage successfully in the HIV-serostatus disclosure process. Integrated interventions to reduce barriers to trustful and effective communication are needed for HIV-affected men and women in partnerships in which seeking couples-based HIV-counseling and testing (CHCT) is challenging or unlikely. These data offer insights to support HIV-serostatus disclosure strategies within relationships over time.